2014
DOI: 10.2298/ciceq121009019b
|View full text |Cite
|
Sign up to set email alerts
|

Use of mesoporous MnO2 as a support for immobilization of lipase from Candida rugosa

Abstract: Article Highlights• We used a new mesoporous carrier for immobilization of lipase from Candida rugosa • The amount of enzyme loading on support was reached to 700 units per 1 g of support • The thermal resistance of the enzyme was enhanced by immobilization • The physical adsorption of enzyme to the support was strong Abstract In this study, immobilization of lipase from Candida rugosa on mesoporous manganese dioxide by adsorption was carried out and the effect of three immobilization variables including tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Therefore, enzymes could not work continuously. At the same time, immobilization reaction time should be optimal for the prevention of losing time during the immobilization [22]. The immobilization process should be done as quickly and efficiently as possible.…”
Section: Effect Of Reaction Time On Immobilizationmentioning
confidence: 99%
“…Therefore, enzymes could not work continuously. At the same time, immobilization reaction time should be optimal for the prevention of losing time during the immobilization [22]. The immobilization process should be done as quickly and efficiently as possible.…”
Section: Effect Of Reaction Time On Immobilizationmentioning
confidence: 99%
“…Details concerning these assays can be found in the Supplementary Material, Item 4. Several authors attributed this effect to the thermal inactivation of enzymes 40–42 . In particular, some authors reported that temperatures higher than 30°C favored the inactivation of free and grafted HRP 17,18,43 .…”
Section: Resultsmentioning
confidence: 99%
“…Several authors attributed this effect to the thermal inactivation of enzymes. [40][41][42] In particular, some authors reported that temperatures higher than 30 C favored the inactivation of free and grafted HRP. 17,18,43 In conclusion, obtained results demonstrate that immobilization conditions corresponding to MAH95 20 were the most favorable among the tested ones to obtain electrospun nanofiber matrices with high peroxidase activity.…”
Section: Evaluation Of Orange II (Oii) Removal By the Developed Matricesmentioning
confidence: 99%
“…Lipases (triacylglycerol acyl hydrolases, EC 3.1.1.3) are largely used as biocatalysts in biotechnology and modern chemistry [ 7 ]. These enzymes are also catalyzing several reactions like esterification [ 8 ], transesterification, acidolysis, interesterification, alcoholysis, aminolysis, oximolysis, thiotransesterification and ammoniolysis in anhydrous organic solvents [ 9 ]. Lipase is widely found in animals, plants and microorganisms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%